Pop Trade Policy – Some Reflections on the Current Trade Policy of the US - Erdey, László; Tőkés, Tibor (International Journal of Engineering and Management Sciences, 2019)
After a brief review of the antecedents our paper aims to systematically organize the recent and current changes in the trade policy of the United States in three broader areas: her changing attitudes towards TPP and WTO, the renegotiation of the North American Free Trade Agreement and the trade war being fought, mostly against China. Our goal is to relate these changes to the trade policy of the former presidential terms, to understand them in the framework of populism and that of the economic policy questions solved only by the second best answer, that is, by protectionism.